Investments in Russia’s transport infractructure - A. A. Bychkova (Вестник университета)
The article considers the investment sources in transport, justifies the need for financial investments on the example of costs on a global and Russian scale. The dynamics of changes in investments by categories of transport routes for 2016–2019 has been analysed. The research of the authors’scientific works on this topic has been given. Renovation and optimisation of the transport structure brings a number of advantages to the Russian transport infrastructure. In addition to the positive aspects of infrastructure modernisation, there is a percentage of losses – these are risks from investments. The methodology of the study presents formulas for calculations, by which the investment programs profitability has been determined. As a solution to the lack of investment funds, the creation of aggregate investment sources has been proposed.